Draft Annual Plan 2008-09 Volume-III (Statements) Government of Andhra Pradesh - Planning Commission (Planning Commission, 2008)
Sector-wise Proposed Outlays Head of Development wise Proposed Outlays Scheme-wise Proposed Outlays Externally Aided Projects Proposed Outlays Centrally Sponsored Schemes Proposed Outlays Tribal Sub-Plan Proposed Outlays Scheduled Caste Sub-Plan Proposed Outlays.
Planning Department, Government of Andhra Pradesh